New Robotic Motion Generation using Digital Convolution with Physical System Limitation - Lee, Geon; Yi, Byung-Ju; Kim, Doik; Choi, Youngjin (2011 50TH IEEE CONFERENCE ON DECISION AND CONTROL AND EUROPEAN CONTROL CONFERENCE (CDC-ECC), 2011)
This paper proposes a novel trajectory generation method considering physical system limitations such as maximum velocity, acceleration, and jerk. Also, the trajectory generation method uses a digital convolution for reducing computational load in robotic motion applications. The method to be proposed has several advantages; first, a continuously differentiable trajectory is simply obtained by applying successive convolution operations. Second, a resultant trajectory is always generated satisfying the given physical system limits. Third, the suggested method has low computational load thanks to recursive form of convolution operation. The effectiveness of the proposed method is shown through numerical simulations.